The Bi-Objective Master Physician Scheduling Problem - GUNAWAN, Aldy (Institutional Knowledge at Singapore Management University, 2010)
Physician scheduling is the assignment of physicians to perform different duties in the hospital timetable. In this paper, the goals are to satisfy as many physicians’ preferences and duty requirements as possible while ensuring optimum usage of available resources. We present a mathematical programming model to represent the problem as a bi-objective optimization problem. Three different methods based on ε–Constraint Method, Weighted-Sum Method and HillClimbing algorithm are proposed. These methods were tested on a real case from the Surgery Department of a large local government hospital, as well as on randomly generated problem instances. The strengths and weaknesses of the proposed methods are also discussed. Finally, a summary is given together with suggestions for future research.